2021
DOI: 10.1039/d1nr06588b
|View full text |Cite
|
Sign up to set email alerts
|

Green-to-UV photon upconversion enabled by new perovskite nanocrystal-transmitter-emitter combination

Abstract: The first example of green (λ > 500 nm)-to-ultraviolet (λ < 400 nm) triplet–triplet annihilation-based photon upconversion sensitized by lead halide perovskite nanocrystals is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Previous studies demonstrated TTA-UC in metal chalcogenide (PbS/Se, ,,, CdSe ,, ) and silicon nanocrystals. Recent studies have shown that upconversion can be sensitized by perovskite quantum dots. However, there is still debate in the literature regarding the exact mechanisms of energy transfer in the overall TTA-UC process, partly due to the complex and ill-defined nature of the nanocrystal–molecule interface . Additionally, the role of surface traps and midgap states has been argued to have both favorable , and unfavorable ,,, effects on the overall upconversion efficiency, further complicating the picture.…”
Section: Recent Applications Of Singlet and Triplet Energy Transfermentioning
confidence: 99%
“…Previous studies demonstrated TTA-UC in metal chalcogenide (PbS/Se, ,,, CdSe ,, ) and silicon nanocrystals. Recent studies have shown that upconversion can be sensitized by perovskite quantum dots. However, there is still debate in the literature regarding the exact mechanisms of energy transfer in the overall TTA-UC process, partly due to the complex and ill-defined nature of the nanocrystal–molecule interface . Additionally, the role of surface traps and midgap states has been argued to have both favorable , and unfavorable ,,, effects on the overall upconversion efficiency, further complicating the picture.…”
Section: Recent Applications Of Singlet and Triplet Energy Transfermentioning
confidence: 99%
“…2). CBDAC and TIPS-Nph showed 0–0 emission peaks at 557 nm (2.23 eV) and 586 nm (2.12 eV), 38 respectively. Good agreement was found between the DFT calculation and experimental results for the T 1 energy level of CBDAC.…”
mentioning
confidence: 99%
“…34−36 In several cases, different sensitizer systems have also been introduced to realize better solid-state upconverters such as semiconductor quantum dots 37,38 and more recently perovskites nanocrystals. 10,12,39 From a general perspective, regardless of the nature of the sensitizer and annihilator moieties employed, the confinement in colloidal nanostructures of both the optically active components is a winning approach in mitigating at least the diffusion dependency of the TTA yield (i.e., half of the problem) by exploiting the confined-TTA process. 40 This mechanism can be observed when triplets are sensitized and physically confined in discrete volumes that are smaller than the space potentially explored by their random diffusion.…”
mentioning
confidence: 99%
“…As shown in Figure A, generally in this case, the photon upconversion is the result of the fusion of the metastable triplet state of two different annihilator/emitter molecules upon diffusion-mediated collision (i.e., an intermolecular TTA), which results in the formation of a high-energy singlet excited state that decays radiatively. The emitter triplets are populated via energy transfer (ET) from the triplets of a low-energy absorbing molecule (or functionalized nanocrystal), that is, a light-harvester/sensitizer. Due to its excellent yield in optimized systems surpassing 30%close to the thermodynamic limit of 50%under low excitation intensity comparable to the solar irradiance, , and considering its efficiency also under noncoherent light, the s TTA-UC surpasses the limitations of traditional photon upconversion mechanisms, such as two-photon absorption or sequential excited-state absorption, that requires coherent and/or high-intensity radiation to be efficient. , For such reasons, the s TTA-UC is intensively investigated to provide a breakthrough in solar technologies, , low power bioimaging, , optogenetics, anticounterfeiting, and oxygen sensing applications . Nevertheless, achieving s TTA-UC in the solid statewhich is more technologically manageable to make devicesis still an open challenge.…”
mentioning
confidence: 99%
See 1 more Smart Citation